TINJAUAN YURIDIS TERHADAP PASAL 17 PERATURAN KEPOLISIAN NOMOR 4 TAHUN 2020 TENTANG PENGAMANAN SWAKARSA - Gadis Nindy Ramadhon (2021)
Perpol No. 4/2020 about Pam Swakarsa changes the color of the security guard uniform to brown like the clothes of the Police. This journal identifies differences in uniform and authority between the security guard and the police as well as the monitoring mechanism for the security guard after the enactment of the Pam Swakarsa Perpol. This research is a normative juridical study with a legal approach and a historical approach. The results obtained are from the similarities between the security guard and police uniforms, there is a difference in the form of a 20% color gradation on the security guard uniform and different attributes. The difference in authority is that the security guard has the authority to take limited preemptive, preventive, and repressive actions, namely in the form of non-judicial actions in his work environment. Meanwhile, the Police have the authority to carry out investigative and investigative actions that apply throughout the territory of Indonesia. The monitoring mechanism carried out on the security guard after the implementation of the Perpol Pam Swakarsa is in the form of supervision, assistance, monitoring, and evaluation carried out by the Chief of Police through Ditbinpotmas Korbinmas Baharkam Polri and Ditbinmas Polda.